The evaluation of ontogenetic and vitality structures of Scilla bifolia l. coenopopulations on the territory of Sumy geobotanical region - Kholodkov, Oleksiy (ScienceRise: Biological Science, 2017)
Aim: to establish typical features of ontogenetic and vitality structures of Scilla bifolia coenopopulations in different phytocenoses in the Sumy geobotanical region, to evaluate the dynamics of these structure types in the period 2015–2016 years. Methods: Common geobotanical methods were used at the research. For the determination of ontogenetic spectrums of Scilla bifolia cenopopulations was used ANONS 6 non-commercial program, and for the determination of vitality spectrums and quality types of coenopopulations was used VITAL non-commercial program, elaborated by Y.A. Zlobin. Result: ontogenetic spectrums of all studied Scilla bifolia coenopopulations are bimodal by the one peak on juvenile or immature individuals and the other peak on young generative individuals. According to T.O. Rabotnov classification, all coenopopulations in 2015 were invasive, and in 2016 P1 and P2 remained invasive and P3 became normal. According to L.O. Zhukova classification, all Scilla bifolia coenopopulations in both 2015 and 2016 represented the normal group, and according to L.V. Zhyvotovsky classification, they are all young, because ∆/ω ratio for the period of researches in Scilla bifolia coenopopulations corresponded to the diapason from 0,06/0,20 to 0,18/0,52. As to the vitality analysis of Scilla bifolia coenopopulations, two qualitative types of this variety coenopopulations are presented: prospering and balanced. The common feature of the vitality structure of all coenopopulations Scilla bifolia is rather low (up to 13 %) part of individuals of the mean («b») vitality class. For coenopopulations P1 and P3 during two years is typical the predominance of high vitality (class «а») individuals. Conclusions within the Sumy geobotanical region the typical feature of Scilla bifolia coenopopulations is similar ontogenetic spectrums. Active renewal processes and intensive introduction in forest groups are inherent to them. Vitality structure of Scilla bifolia coenopopulations changes at the transfer from one phytocenosis to another. It is an evidence of realization of the ability to adaptation and to adjustment to growth conditions